Cultural memory in Republican and Augustan Rome - Dinter, Martin 1950-; Guérin, Charles 1978- (Cambridge University Press, 2023)
"Cultural memory theory explains why, how, with what results we remember certain information. This book explores these questions in relation to late Republican and Augustan Rome and provides an excellent and accessible starting point for readers who are new to the topic, whilst also appealing to the seasoned scholar"--